(untitled) (Global Journal of Science Frontier Research, 2020)
Contemporary built environments experience a vast number of factors due to globalization, which effected and influenced how the built form is generated and used. The relationship between the urban and the building levels is a crucial aspect that needs a thorough investigation to understand how these two levels can integrate and complement the built environment’s overall identity. This paper examines the concept of access and its location within the urban fabric and how an access influenced the formation of physical and nonphysical threshold spaces to overcome the number of socio-cultural issues. Space Syntax convex map and justified access graphs were used to understand the connectivity, density, and integration of the access and the threshold space in relation to the overall built form.